Extreme Rainstorm-Induced Cascading Vulnerability in Cross-Border Metro Networks: A Modeling Framework for Shenzhen-Hong Kong - Meng, Yangyang; Zhao, Xiaofei (Proceedings of the International ISCRAM Conference, 2026)
Extreme rainstorms increasingly threaten cross-border metro systems whose interdependencies may amplify localized disruptions into systemic failures. This study proposes a network-based cascading vulnerability assessment framework for cross-border metro networks, motivated by the Shenzhen-Hong Kong system. The model integrates rainstorm-induced initial failures, probabilistic structural interdependency, dynamic load redistribution, and overload-driven cascading dynamics. A multidimensional vulnerability metric system quantifies structural, functional, and cascading impacts, together with a coupling-induced amplification factor. Conceptual validation on a dual-layer simplified network shows that cross-border coupling significantly amplifies system-wide degradation and exhibits threshold-like redundancy behavior. Compared with existing studies, this study identifies cross-border connectors as systemic vulnerability amplifiers and underscores the need for coordinated redundancy planning. Future work will extend the model to empirically grounded network data and spatially explicit rainfall scenarios. This study contributes to interdependent infrastructure risk modeling and provides a decision-support foundation for coordinated cross-border crisis management and resilience planning under extreme climate events.